2018
DOI: 10.1007/s11869-018-0631-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EU air quality standards through modeling and the FAIRMODE benchmarking methodology

Abstract: We evaluate air quality modeling over the East Mediterranean using the benchmarking methodology developed in the framework of the Forum for Air Quality Modelling in Europe (FAIRMODE). FAIRMODE aims to provide a harmonized approach of model evaluation for regulatory purposes. We test the methodology by assessing the performance of the Weather Research and Forecasting model coupled with chemistry (WRF-Chem) against ground-based air quality observations over Cyprus, a member state of the European Union. Two neste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Due to these limitations, we support the refinement of combined air pollution exposure assessment methods, including the integration of measured and modeled atmospheric data. As examples, the Community Multiscale Air Quality (CMAQ) model is a multipollutant, deterministic modeling system with temporal and spatial flexibilities, and the Forum for Air Quality Modelling in Europe (FAIRMODE) is a network that strives to harmonize the use of air pollution assessment practices [38,39]. More robust data integration methods will strengthen the accuracy and precision of air pollution exposure assessment, including for wildfire smoke that is becoming more prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these limitations, we support the refinement of combined air pollution exposure assessment methods, including the integration of measured and modeled atmospheric data. As examples, the Community Multiscale Air Quality (CMAQ) model is a multipollutant, deterministic modeling system with temporal and spatial flexibilities, and the Forum for Air Quality Modelling in Europe (FAIRMODE) is a network that strives to harmonize the use of air pollution assessment practices [38,39]. More robust data integration methods will strengthen the accuracy and precision of air pollution exposure assessment, including for wildfire smoke that is becoming more prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating the modeled atmospheric concentrations, a number of statistical parameters were considered. Spatial correlation coefficient (r), standard deviation (SD), and mean bias (MB) values are commonly used by the modeling community (e.g., Baldasano et al, 2011;Im et al, 2018;Monteiro et al, 2018;Kushta et al, 2019, among many others) and were therefore selected according to the criteria of . Spatial-r is used to assess the ability of the model to capture the spatial pattern of D5 observations.…”
Section: Model Evaluation With Field-based Datamentioning
confidence: 99%
“…In addition, EDGAR was considered as a validation basis for studies related to emissions of different pollutants using various modeling approaches (Dentener et al 2002;Bergamaschi et al 2010). However, a comparison between EDGAR and national developed emission inventories showed that even though EDGAR can be applicable for continental-scale modeling, it is not recommended for regional to local air quality simulations, and a more complete and up-to-date national emission inventory should be used instead (Madrazo et al 2018;Puliafito et al 2017;van Amstel et al 1999;Hristov et al 2017;Liousse et al 2019;Georgiou et al 2020;Kushta et al 2019).…”
Section: Introductionmentioning
confidence: 99%